2008
DOI: 10.1007/s00535-008-2199-0
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytapheresis for the treatment of active pouchitis: a pilot study

Abstract: Leukocytapheresis therapy could be a new therapeutic strategy for patients with pouchitis after ileal pouch-anal anastomosis for ulcerative colitis. These encouraging results lead us to propose a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…However, the long‐term effectiveness of anti‐TNF‐alpha antibody has not been well studied, and other treatment options are currently being sought. An open‐label study consisting of eight patients only showed possible short‐term effectiveness of cytapheresis for the treatment of pouchitis and no adverse effects were observed in this study. Thus, cytapheresis may be applied to the treatment of pouchitis, although the current evidence is not sufficient to make any concrete conclusions.…”
Section: Management Of Pouchitismentioning
confidence: 61%
“…However, the long‐term effectiveness of anti‐TNF‐alpha antibody has not been well studied, and other treatment options are currently being sought. An open‐label study consisting of eight patients only showed possible short‐term effectiveness of cytapheresis for the treatment of pouchitis and no adverse effects were observed in this study. Thus, cytapheresis may be applied to the treatment of pouchitis, although the current evidence is not sufficient to make any concrete conclusions.…”
Section: Management Of Pouchitismentioning
confidence: 61%
“…One study evaluated the efficacy of another type of leukocytapheresis with Cellsorba filter column (LCAP) in active pouchitis [Araki et al 2008]. A total of eight patients received LCAP weekly for 5 weeks along with baseline therapy including an antibiotic (metronidazole), probiotics, 5-ASA or corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of white blood cells from circulation by means of leucocytapheresis has been reported as a potential therapy for patients with active pouchitis 26. Eight patients were treated in an open-label treatment protocol, six of whom achieved remission with no adverse reactions observed.…”
Section: Treatment Of Pouchitismentioning
confidence: 99%